Morphological characterization and electronic properties of pristine and oxygen-exposed graphene nanoribbons on Ag(110). Issue 13 (6th January 2021) - Barcelon, Jose Eduardo; Smerieri, Marco; Carraro, Giovanni; Wojciechowski, Pawel; Vattuone, Luca; Rocca, Mario; Nappini, Silvia; Píš, Igor; Magnano, Elena; Bondino, Federica; Vaghi, Luca; Papagni, Antonio; et al.
Abstract : Graphene nanoribbons (GNRs) are at the frontier of research on graphene materials since the 1D quantum confinement of electrons allows for the opening of an energy gap. Abstract : Graphene nanoribbons (GNRs) are at the frontier of research on graphene materials since the 1D quantum confinement of electrons allows for the opening of an energy gap. GNRs of uniform and well-defined size and shape can be grown using the bottom-up approach, i.e. by surface assisted polymerization of aromatic hydrocarbons. Since the electronic properties of the nanostructures depend on their width and on their edge states, by careful choice of the precursor molecule it is possible to design GNRs with tailored properties. A key issue for their application in nanoelectronics is their stability under operative conditions. Here, we characterize pristine and oxygen-exposed 1.0 nm wide GNRs with a well-defined mixed edge-site sequence (two zig-zag and one armchair) synthesized on Ag(110) from 1, 6-dibromo-pyrene precursors. The energy gap and the presence of quantum confined states are investigated by scanning tunneling spectroscopy. The effect of oxygen exposure under ultra-high vacuum conditions is inferred from scanning tunneling microscopy images and photoemission spectra. Our results demonstrate that oxygen exposure deeply affects the overall system by interacting both with the nanoribbons and with the substrate; this factor must be considered for supported GNRs under operative conditions.